Segurança no trabalho com agrotóxicos em citros: aplicação com o turbopulverizador e preparo de calda em tanque de 2.000 L - Oliveira, Maurício Leite De; Machado Neto, Joaquim Gonçalves [UNESP] (Fundação Jorge Duprat Figueiredo de Segurança e Medicina do Trabalho - FUNDACENTRO, 2003)
The objectives of this study were: a) to quantify dermal and respiratory exposure resulting from work conditions in the application of pesticides on citrus crops using a air-assisted sprayer and by preparing the spray in a tank with a capacity of2.000 L; b) to evaluate the measures of individual protection for these workers; c) to determine the areas of the worker's body most exposed; and d) to classify the work conditions with and without the protective measures tested, with regard to the occupational safety of the recommendations for the pesticides used in controlling the main pests and diseases of this crop. It was shown that for the tractor driver and sprayer operator applyng pesticides on citrus trees, the most efficient protective measures were the AZR ensemble and the Real cabin. The AZR ensemble was effective in controlling exposure of the spray preparer, because it was sufficient to turn work conditions from unsafe to safe. The area of the body most exposed under the two work conditions studied was the hands of the workers.

Os objetivos deste trabalho foram quantificar as exposições dérmicas e respiratórias proporcionadas pelas condições de trabalho na aplicação de agrotóxicos em cultura de citros com o turbopulverizador e no preparo de caldas em um tanque de 2.000 L de capacidade; avaliar a eficiência de medidas de proteção individual; determinar as regiões mais expostas do corpo dos trabalhadores e coletiva para esses trabalhadores; e classificar as condições de trabalho, sem e com as medidas de proteção testadas, quanto à segurança ocupacional das recomendações de agrotóxicos registrados para o controle das principais pragas e doenças dessa cultura. Verificou-se, que para o tratorista e para o aplicador, pulverizando agrotóxicos em citros com o turbopulverizador, as medidas de proteção mais eficientes foram o conjunto AZR e a cabina Real. O conjunto AZR foi eficiente no controle da exposição do preparador de caldas, pois foi suficiente para tornar condições de trabalho inseguras em seguras. A região mais exposta do corpo, nas duas condições de trabalho estudadas, foram as mãos dos trabalhadores.
Work safety in the use of pesticides in citrus: application with an air-assisted sprayer and preparation of spray in a 2.000-L tank
Keywords: Pesticide; Dermal Exposure; Respiratory Exposure; Citrus; Agrotóxicos; Exposição dérmica; Exposição respiratória; Cítrus